Pengaruh Transparansi, Akuntantabilitas, dan Partisipatif Pemerintah Desa terhadap Pengelolaan Keuangan di Kecamatan Tanggul, Kabupaten Jember - Muhammad Muhibudin; Agustin Hari Prastyowati; Wiwik Fitria Ningsih (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
Government accounting is one of the fields of accounting that specializes in recording and reporting transactions that occur in government agencies. The existence of demands for accountability and transparency on the recording of transactions, and reporting of government performance by interested parties makes government accounting a necessity that is no longer inevitable today. Villages have an important role, especially in carrying out tasks in the field of publicservices. Therefore, it is necessary to know the extent of transparency, accountability and participation in village financial management considering that this is very closely related to the continuity of the welfare of the wider community. This studiaims to analyze the effect of transparency, accountability, and government participation on village financial management (case studion Tanggul Sub-distric, Jember district. The data that used in this research is primary data. The method that researcher used is survey method with quantitative approach. The reseacher used SPSS version 24 to test the data. Based on data analysis, the conclusion of this studiare partially there are not significant effect of accuntabily and government participation to village financial management, while transparency has significant effect to village financial management. Simultaneously transparency, accuntabulity, and government participation have significant effect to village financial management.